Le syndicalisme de cadres et la législation québécoise du travail - Chartier, Roger (Relations industrielles / Industrial Relations, 1965)
No matter how one feels about supervisory and managerial. unionism, this level of organization must be pitted, as both concept and fact, against the larger context of law, sociology, economics, politics and business administration in a given society. This essay will develop no thesis, « pro » or « con ». It will lay emphasis on thelegal aspects, hoping for others to indicate, through careful research, the important differences (social, political, economic and administrative) existing between the European context (in which some form of supervisory and managerial unionism flourishes) and the North-American one (in which such unionism is practically non-existent).